The Incremental Information Content of the Accrual and Funds Components of Earnings After Controlling for Earnings. - Wilson, G. Peter (The Accounting Review, 1987)
ABSTRACT: This study investigates whether the accrual and funds components of earnings have incremental information content beyond earnings itself. The research design is motivated by the insight that earnings and revenues are announced in the Wall Street Journal before the annual report, which contains both accrual and funds items, is released. This allows a direct measurement of the incremental information content of the accrual and funds components of earnings which is not possible when these releases are treated contemporaneously. This study finds evidence of an association between stock returns, measured over a short interval covering the date the annual reports arrive at the SEC, and new information about the cash and noncash components of earnings released at that time. By itself, this result implies that at least one of these components has Information content. After controlling for earnings, incremental information about the cash and noncash components of earnings is precisely the same.